High-Performance Health Financing for Universal Health Coverage : Driving Sustainable, Inclusive Growth in the 21st Century - World Bank Group (World Bank, Washington, DC, 2019)
The majority of developing countries will fail to achieve their targets for Universal Health Coverage (UHC) and the health- and poverty-related Sustainable Development Goals (SDGs) unless they take urgent steps to strengthen their health financing. The UHC financing agenda fits squarely within the core mission of the G20 to promote sustainable, inclusive growth and to mitigate potential risks to the global economy. Closing the substantial UHC financing gap in 54 low and lower middle-income countries will require a strong mix of domestic and international investment. G20 Finance Ministers and Central Bank Governors can help countries seize the opportunities of high-performance health financing by adopting and steering a UHC financing resilience and sustainability agenda.